Coalition game theoretic P2P trading in a distribution network integrity-ensured local energy market - M., Imran Azim (2023)
This paper presents a peer-to-peer (P2P) trading-enabled local energy market (LEM) mechanism and analyses it in the Australian market context to verify its feasibility. To do so, a coalition game theoretic-model is adopted to model the mutual trading interactions between participating purchasers and sellers in the LEM, in which energy is purchased/sold at a rate lower/higher than the business-as-usual purchase/sell price while the margin of the LEM operator is locked on. Further, both purchased and sold energy quantities are also decided on following the import, export, voltage, and line flow constraints, respectively, prescribed for the P2P trading in the LEM. The properties of the proposed coalition game are examined, and the beneficial aspects and stability of the structured P2P coalition are guaranteed. Besides, an algorithm is proposed to formulate energy contract and pricing mechanisms in the P2P coalition-structured LEM, and to distribute the economic benefit among the LEM participants efficiently. Finally, extensive simulation results are demonstrated to validate the structured P2P trading-based LEM strategy in the context of the Australian market and distribution network. The simulation results confirm that participants, both sellers and purchasers, can decrease their energy costs substantially, and the LEM operator can also secure its margin while the distribution network voltages and line congestion are within the prescribed ranges.